Translucency of a Dental Porcelain Mixed by Two Ceramic Slurry Methods: A Bayesian Comparison - Catalina Serna-Meneses; Gabriel Ocampo-Parra; Santiago Arango-Santander; Claudia Garcia-Garcia; Luis Felipe Restrepo-Tamayo; Johnatan Cardona-Jimenez; Alexander Ossa; Alejandro Pelaez-Vargas (Hindawi Limited, 2022)
Background. The ceramics industry produces porcelain pastes using a controlled ratio of water and porcelain powder. Two methods are used to produce a dental porcelain paste: one-step mixing or incremental mixing. Objective. To evaluate the optical properties of a feldspathic dental ceramic using two different ceramic paste preparation methods using a Bayesian approach. Materials and Methods. Two groups of feldspathic porcelain discs, an incremental mixing group (n = 40) and a one-step mixing group (n = 40), were assessed. Groups were evaluated using spectrophotometry, and the translucency parameter (TP) of each sample was calculated. Surfaces were characterized by AFM and SEM. Statistical analysis was performed using a Bayesian approach. Results. Translucency parameter values of the incremental mixing group ranged from 1.65 to 3.41, while values for the one-step mixing group ranged from 3.62 to 5.74, this difference being statistically significant. The lowest roughness was obtained on the surface of discs in the one-step mixing group. Conclusions. Feldspathic porcelain with lower translucency and higher roughness was obtained using the incremental mixture method.